CompTIA security+ (SY0-701) - Bryan, Wes; Sequeira, Anthony; Lowrie, Daniel; Goodwin, Sophie (Packt Publishing, 2023)
This course begins with core cybersecurity concepts, creating a solid base for in-depth security management study. It dives into security principles, authentication factors, and control types, establishing fundamental cybersecurity knowledge. The course covers topics such as Zero Trust, physical security, and encryption complexities, including Public Key Infrastructure and digital certificates. The course also explores the diverse threat landscape, from social engineering to cloud and virtualization vulnerabilities, providing a comprehensive understanding of cyber threats. The course investigates various attack indicators, like malware and network attacks, boosting your threat identification and response capabilities. Key security infrastructure elements, including firewalls and secure communication, are discussed. The course also emphasizes practical applications in identity and access management, wireless security, and network device security. Vulnerability analysis and digital forensics are examined, readying you for both proactive and reactive cybersecurity roles. Concluding with governance, risk management, and compliance, this course prepares you for real-world cybersecurity challenges, making it a crucial tool for aspiring professionals. What you will learn Understand security control categories Learn Zero Trust and physical security Explore encryption and PKI solutions Identify and mitigate digital threats Secure networks and communication Implement comprehensive cybersecurity measures Audience This course is ideal for IT professionals, security analysts, network administrators, and anyone aspiring to specialize in cybersecurity. A foundational understanding of IT and basic security concepts is recommended. The course is perfect for those seeking to enhance their cybersecurity skills and apply them in various IT and network security roles. About the Authors ACI Learning: ACI Learning train leaders in Cybersecurity, Audit, and Information Technology. Whether you're starting your IT career, mastering your profession, or developing your team, they're with you every step of the way. Wes Bryan: Wes Bryan, our Edutainer, began his IT journey in 2009 and transitioned into IT instruction. He earned global teaching awards three times during his early teaching years and holds certifications including CompTIA A+, Network+, Security+, Server+, Cloud+, CySA+, MCSA, MTA, MCTS, MCP, MS, and MCT. Anthony Sequeira: Anthony Sequeira, our Edutainer, boasts a robust IT career since 1996 and a love for technology from various vendors. His extensive certifications cover CCIE R&S #15626, AWS, Cisco, CompTIA, Juniper, and Microsoft. Daniel Lowrie: Daniel Lowrie, our show host, shifted to IT education after successful roles as a systems administrator and network administrator. His certifications include CompTIA A+, Network+, Linux+, CySA+, PenTest+, CEH, MCSA, CFR, and eJPT. Sophie Goodwin: Sophie Goodwin, with 8+ years of experience as a film and voice talent, enriches our team with on-camera and voice-over expertise spanning eLearning content, independent films, TV & web commercials, and video games. Her qualifications include a Bachelor of Science in Telecommunication and (ISC)² CC certification in Cybersecurity.
Online resource; title from title details screen (O'Reilly, viewed Decenber 19, 2023)
Keywords: Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Examinations -- Security measures; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Examens; Sécurité; Mesures; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet